(untitled) (Journal of Asian Development Studies, 2025)
The present research is organised to investigate the reasons behind the changing pattern of crop yields in a labour-rich and underdeveloped economy, where agriculture plays a primary role in economic activity. The cropping sector alone contributes around 33.95% to the total output of the agriculture sector, which was recorded at 8975069 million during the fiscal year 2022-23. The livestock and cropping sectors jointly contribute 96.32% to the agricultural sector’s output [Pakistan Economic Survey, 2023–2024]. This highlights the importance of the cropping sector, which is crucial in determining the performance of the agricultural industry. After utilising the ARDL bounds test on the data series from 1972 to 2022, this research reveals an inverted U shaped relationship between fertiliser consumption and crop yield, while urban population, agricultural machinery, and rents from natural resources significantly accelerate the yield of the cropping sector. These results emphasise the need to utilise environmentally sustainable and scientifically advanced fertilisers to the extent that crop production reaches its maximum potential. This research further proposes that the adoption of advanced and ecologically supportive technology is encouraged among farmers to boost crop yields. This research further recommends promoting the size of rents from natural resources by increasing investments in natural resources to stimulate crop production in Pakistan. This study also suggests transferring the surplus workforce from the rural sector to cities, so that the burden in terms of production costs on agriculture should decrease. This will enhance profits for farmers, which will be reinvested to increase crop yields further.